Maternal and Early Childhood Risk Factors for Overweight and Obesity among Low-Income Predominantly Black Children at Age Five Years: A Prospective Cohort Study. (29th September 2012) - Janjua, Naveed Zafar; Mahmood, Bushra; Islam, M. Aminul; Goldenberg, Robert L.
Abstract : Objective . To identify maternal and early childhood risk factors for obesity and overweight among children at age 5 in the state of Alabama. Methods . We recruited 740 mothers during early pregnancy from University of Alabama Prenatal Clinics in a prospective cohort study and followed them throughout pregnancy. We followed their children from birth until 5 years of age. The main outcome measure was obesity (BMI for age and sex ≥ 95th percentile) at 5 years of age. We used poisson regression with robust variance estimation to compute risk ratio (RR). Results . At the 5th year of followup, 71 (9.6%) of the children were obese and 85 (11.5%) were overweight (BMI ≥ 85th–<95th percentile). In multivariable analysis, maternal prepregnancy overweight (RR: 2.30, 95% CI: 1.29–4.11) and obesity (RR: 2.53, 95% CI: 1.49–4.31), and child's birth weight >85th percentile (RR: 2.04, 95% CI: 1.13–3.68) were associated with childhood obesity. Maternal prepregnancy BMI, birth weight, and maternal smoking were associated with the child being overweight 1–12 cigarettes/day versus 0 cigarettes/day (RR: 1.40, 95% CI: 1.02–1.91). Conclusion . Children of overweight and obese mothers, and children with higher birth weight, are more likely to be obese and overweight at age 5. Maternal smoking 1–12 cigarettes per day is associated with the child being overweight.